The Role of Green Libraries and Sustainable Practices for Sustainable Development Goals (SDGs) in Nigeria - Dada, Kayode Sunday John (Information Research Communications, 2025)
Objectives/Context: Green libraries represent a paradigm shift in library management, integrating eco-friendly practices to support the United Nations Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), and SDG 13 (Climate Action). Materials and Methods: This mixed-methods study assessed the implementation of green library practices in 10 selected institutions across Lagos, Abuja, and Ilorin, Nigeria, surveying 205 library professionals (82% response rate) using a validated 5-point Likert-scale questionnaire (Cronbach’s alpha=0.82) and supplementing with interviews. Stratified random sampling ensured regional representation (40% Lagos, 30% Abuja, 30% Ilorin), with data collected in 2025 and analyzed via SPSS v.26 for descriptive statistics and NVivo 12 for thematic analysis. Ethical approval was obtained from the University of Abuja Institutional Review Board. Results: Results indicated moderate overall adoption, with a grand mean score of 3.27 (SD=0.38). Waste Reduction and Recycling scored highest (M=3.56, SD=1.26), reflecting effective recycling programs in urban areas like Lagos (M=4.00). Energy Conservation, Sustainable Building Design, and End-of-Life Resource Management each achieved M=3.44. Digital Resource Expansion (M=2.78, SD=1.47) and Community Engagement for Climate Literacy (M=2.56, SD=1.42) lagged. Regional disparities were notable: Lagos led (M=3.48), followed by Abuja (M=3.22), and Ilorin (M=2.67). Conclusion/Recommendation: These findings highlight uneven sustainability efforts, driven by funding constraints and infrastructural challenges. One key recommendation is for policymakers to prioritize federal funding for solar installations and digital infrastructure upgrades in underperforming regions to enhance uniform adoption.
Keywords: Environmental sustainability; Green libraries; Nigeria; SDGs; Sustainable practices.